The Potential of RQANI for Shaping Preservice Biology Teachers’ Character at Islamic University - Astuti Muh Amin (AL-ISHLAH: Jurnal Pendidikan, 2023)
It is essential to support students' character development as part of the learning process to prepare the next generation for global challenges. This study aimed to determine the impact of the RQANI model on the character of biology students. This quasi-experimental study employed a nonequivalent control group design. The research population was all biology education students in the City of Ternate, North Maluku, Indonesia. The research sample consisted of 120 students from the biology education department at IAIN Ternate and STIKIP Kie Raha located in the City of Ternate. Participants’ character was assessed using a valid and reliable instrument. Data analysis was performed using ANACOVA at 5% significance level. The analysis results showed that the RQANI model had a positive impact on students’ character. This study’s findings are expected to benefit lecturers and teachers in their efforts to improve the character of students and the quality of learning in the classroom.